Artificial Intelligence (AI) in Film Script Writing - Riski, Wahyu Nova; Abidin, Zainal (Seni Media Rekam ISI Surakarta, 2024)
Artificial intelligence has influenced various aspects of human life in recent years. The film industry is no exception to be affected by the expansion of artificial intelligence. Focusing on the process of short movie scenario development, this research aims to explore the extent to which artificial intelligence or AI can play a role in the creative process of filmmaking. This research uses an innovative exploration method using action research methods with a special focus on the art-based action research approach. Using three experimental cycles, this research found that artificial intelligence has a series of limitations in its function to assist the film script creation process, therefore, it is unlikely that artificial intelligence can replace humans completely soon. However, this research found that despite all its limitations, artificial intelligence has a significant role in helping film creators simplify the initial steps of the film script development process, if it is utilized in the right way. This research makes a substantial contribution to the discussion regarding the use of artificial intelligence in the filmmaking creative process. Keywords: film, screenplay, artificial intelligence, AI